Oxygen Depletion Events Control the Invasive Golden Mussel (Limnoperna fortunei) in a Tropical Floodplain - Oliveira, Márcia D.; Hamilton, Stephen K.; Calheiros, Debora F.; Jacobi, Claudia M. (Wetlands (Wilmington, N.C.), 2010)
Over the past 10 years the golden mussel ( Limnoperna fortunei ), an exotic species native to eastern Asia, has become widespread and abundant in the Pantanal Wetland, Brazil. Oxygen concentrations are often low in rivers and floodplain waters of the Pantanal and oxygen depletion events can last for several weeks during the rising water phase. Although mortality of L. fortunei has been documented during oxygen depletion events, its tolerance to hypoxic and anoxic conditions is poorly understood, in part because changes in oxygen availability are accompanied by other changes such as decreased pH. We analyzed interannual variation in densities of adults and juveniles in relation to varying oxygen conditions, and tested the tolerance of L. fortunei to oxygen depletion events in a floodplain lake and in the laboratory. Mussels died after 5 days of an oxygen depletion event in a floodplain lake, and a population established there in 2005 was extirpated in 2006 owing to hypoxic conditions. Laboratory tests confirmed that mussels died more quickly in water from the oxygen depletion event. Annual oxygen depletion events must control the density of the invasive golden mussel in the Pantanal, maintaining low densities and periodically extirpating them from some habitats.